Biochemical and antigenic characterization of the structural proteins and their post-translational modifications in purified SARS-CoV-2 virions of an inactivated vaccine candidate. Issue 1 (1st January 2020) - Zhang, Xiao-Yu; Guo, Jing; Wan, Xin; Zhou, Jin-Ge; Jin, Wei-Ping; Lu, Jia; Wang, Wen-Hui; Yang, An-Na; Liu, Ding Xiang; Shi, Zheng-Li; Yuan, Zhi-Ming; Li, Xin-Guo; et al.
ABSTRACT: In the face of COVID-19 pandemic caused by the newly emerged SARS-CoV-2, an inactivated, Vero cell-based, whole virion vaccine candidate has been developed and entered into phase III clinical trials within six months. Biochemical and immunogenic characterization of structural proteins and their post-translational modifications in virions, the end-products of the vaccine candidate, would be essential for the quality control and process development of vaccine products and for studying the immunogenicity and pathogenesis of SARS-CoV-2. By using a panel of rabbit antisera against virions and five structural proteins together with a convalescent serum, the spike (S) glycoprotein was shown to be N-linked glycosylated, PNGase F-sensitive, endoglycosidase H-resistant and cleaved by Furin-like proteases into S1 and S2 subunits. The full-length S and S1/S2 subunits could form homodimers/trimers. The membrane (M) protein was partially N-linked glycosylated; the accessory protein 3a existed in three different forms, indicative of cleavage and dimerization. Furthermore, analysis of the antigenicity of these proteins and their post-translationally modified forms demonstrated that S protein induced the strongest antibody response in both convalescent and immunized animal sera. Interestingly, immunization with the inactivated vaccine did not elicit antibody response against the S2 subunit, whereas strong antibody response against both S1 and S2 subunits was detected in the convalescent serum. Moreover, vaccination stimulated stronger antibody response against S multimers than did the natural infection. This study revealed that the native S glycoprotein stimulated neutralizing antibodies, while bacterially-expressed S fragments did not. The study on S modifications would facilitate design of S-based anti-SARS-CoV-2 vaccines.